Five new species of the genus Apanteles Foerster (Hymenoptera: Braconidae: Microgastrinae) from Vietnam - Long, Khuat Dang (Academia Journal of Biology, 2012)
Five new species of two groups of the genus Apanteles Foerster described and illustrated from Vietnam, of which four species Apanteles derivatus Long sp. n., A. flavicentrus Long, sp. n., A.flavigaster Long, sp. n. and A. hatinhensis Long, sp. n. belong to the Apanteles merula - group, one species Apanteles paraglaope Long, sp. n. belongs to the Apanteles ater - group.